P-129 CCFA Quality of Care Breakthrough Series Collaborative: Improving the Delivery of Urgent Care for Patients with IBD. (February 2017) - Hou, Jason; Xu, Ang; Weatherly, Julie; Sellin, Joseph; Kaur, Manreet; Gonazalez, Iliana; Gonzalez, Janette; Cruz, Guillermina; Waddy, Angela; Velani, Shelina; Long, Millie; Jones, Michael; et al.
Abstract : Background: Patients with inflammatory bowel disease (IBD) may have exacerbations of symptoms necessitating urgent medical attention. Due to barriers in access, patients often seek urgent care from emergency departments (ED) for acute symptoms. Unnecessary ED utilization may result in additional cost, overuse of opiates, steroids and radiological studies. The aim of this study was to use a Breakthrough Series (BTS) Collaborative to improve the delivery of urgent care to patients with IBD. Methods: The Crohn's and Colitis Foundation of America's IBD Qorus is a multi-center quality improvement learning health system for IBD. The first phase of IBD Qorus involved 10 academic and community practice sites, which participated in a BTS using the Model for Improvement. The BTS consisted of 3 in-person learning sessions and monthly web-based meetings. Physician and patients identified 15 potential interventions to improve urgent care access, which were shared with all participants. Sites tested selected interventions based on locally identified deficiencies and resources. Data were collected prospectively from patients using paper questionnaires during routine clinical encounters assessing patients' perceptions of urgent care quality, ED visits, CT scans, steroids, and opiate use for the 6 months prior to the clinical visit. This abstract describes the processes and outcomes from one IBD Qorus site, Baylor College of Medicine, using the BTS over a 13 month period. Outcomes were assessed using run charts and stratified based on IBD activity using the Manitoba IBD Index. Results: Through interviews with patients, deficiencies were identified in communicating a specific plan of action during an exacerbation of IBD symptoms, and timely means for routing urgent messages to clinical staff. To address both deficiencies, an "urgent care hotline" was created. This hotline provided patients with direct access to a nurse, and 2 interventions were developed to educate patients on how to access the hotline with guidelines for appropriate use: (1) After-visit summaries using the electronic medical record, and (2) Printed wallet-sized tri-fold cards distributed during routine clinical encounters. There were 1161 IBD patient encounters during the study period, including 6 months of baseline data prior to interventions. Run charts demonstrated shifts in reductions in ED visits, CT scans, and hospital stays, and an increase in patient satisfaction after the interventions. Among patients with inactive IBD, no significant changes were observed. Among patients with active IBD, a shift of increased patient satisfaction in urgent care was observed. Conclusions: Deficiencies in access to urgent care for IBD were identified using a BTS Collaborative, including lack of a plan for urgent communication and lack of timely routing of urgent clinical messages. The creation of a nursing care hotline and patient-education materials were associated with shifts towards improvement in ED utilization, CT scan use, hospitalizations, and patient satisfaction for IBD-related urgent care experiences. Participation in a quality improvement learning health system facilitates improvement in patient care and outcomes.